Kebijakan Hukum Pidana terhadap Kejahatan Narkotika Studi Kasus Putusan Pengadilan Negeri Jambi Nomor: 228/PID.SUS/2022/PN.JMB - Warfian Saputra; Herizal Kurniawan (Wajah Hukum, 2023)
Law No. 35 of 2009 on Narcotics is a substantive criminal policy, which is accompanied by various other legal rules in the process of prosecuting the perpetrators of narcotic crimes in the form of the High Court Edaran Letter No. 04 of 2010 on the placement of abuse, abuse victims and drug addicts in medical rehabilitation institutions and social rehabilitation. The SEMA was distributed by the Supreme Court of the Court of Justice in the criminal justice system so it is expected to be a judge in deciding on the crime of Narcotics. Narcotic crime is the biggest crime that exists in Indonesia so it is necessary to enforce the criminal law wisely and wisely. From the data obtained from the Sub Section of Registration of the Institute of Marketing Class IIA Jambi, the current number of inhabitants is 1.316 People. A total of 757 people were civilians with drug cases and 254 of them were residues of drug cases.